Academic Senate Minutes 2016-02-18 - Academic Senate:::::::::
Chair Report. Agenda – Approved. Minutes delayed. President Report. Provost Report. Vice President of Administration and Finance Report. Vice Chair Report. Revision to the Reappointment, Tenure and Promotion policy approved. Student Affairs Report. Associated Students Report. Statewide Senators Reports. EPC Report. FSAC Report. SAC Report. CFA Report. Staff Report.